2012
DOI: 10.1259/dmfr/13441277
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional visualization of composite fillings for dental identification using CT images

Abstract: Objectives: This study aimed to discriminate between enamel and composite resins by differences in Hounsfield units shown on 16 section multidetector CT (MDCT) images taken of unidentified bodies. Methods: First, we determined the Hounsfield units of composite resins in 15 extracted human teeth. We then filled a single cavity prepared in each of the teeth with one of five different types of composite resins, and scanned the teeth using our routine post-mortem CT protocol for the head and neck. Obtained data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…In our study, subjective visualization suggested that bone crest delineations have a minimal effect on image quality, with scores ranging from 1.75 to 2.30 (fair to good), consistent with the results of a previous study by Koizumi et al 20 The visualization of dentin or enamel was worst ( Table 2), indicating that they are inherently low-contrast structures (the difference between dentin and enamel regions was ,200 HU) 21 and susceptible to changes in exposure setting, especially for tube voltage settings. The visualization of mandibular structures was slightly better than that of maxillary structures, similar to the results presented by Pittayapat et al 22 This might be because most mandibular structures are well corticated.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, subjective visualization suggested that bone crest delineations have a minimal effect on image quality, with scores ranging from 1.75 to 2.30 (fair to good), consistent with the results of a previous study by Koizumi et al 20 The visualization of dentin or enamel was worst ( Table 2), indicating that they are inherently low-contrast structures (the difference between dentin and enamel regions was ,200 HU) 21 and susceptible to changes in exposure setting, especially for tube voltage settings. The visualization of mandibular structures was slightly better than that of maxillary structures, similar to the results presented by Pittayapat et al 22 This might be because most mandibular structures are well corticated.…”
Section: Discussionsupporting
confidence: 90%
“…The increasing demand for CT exams in the routine of medical services triggers a modification in the contemporary AM/PM data, which migrates from the conventional radiographs to more technological imaging modalities. The human identification process benefits from this modification achieving more realistic and reliable comparison of forensic data ( 3 , 9 ). The use of high-tech imaging techniques plays a valuable role in complex cases involving decomposed/charred bodies and skeletal remains, from which soft tissues and fingerprints are frequently damaged ( 5 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beam hardening or 'metal flaring' often obscure not only detail in relation to a tooth but also obscures the dentition or lack of, in the immediate area to the 'flaring'. Work in the area of CT scanning and image manipulation continues to reduce and or overcome these limitations (7,8).…”
Section: Computed Tomography (Ct) Scanning In the Forensic Odontologymentioning
confidence: 99%